Long-term seed aid in Ethiopia: past, present, and future perspectives - International Center for Tropical Agriculture; Ministry of Agriculture and Rural Development, Ethiopia; Ethiopian Institute of Agricultural Research; University of East Anglia; Tigray Agricultural Research Institute; Southern Agricultural Research Institute, Ethiopia; Amhara Regional Agriculture Research Institute (Ethiopian Institute of Agricultural Research, International Center for Tropical Agriculture, and Overseas Development Group, 2007)
This report assesses the effects of emergency seed aid in Ethiopia.